Planar normal sections of focal manifolds of isoparametric hypersurfaces in spheres - Sanchez, Cristian Urbano (2015)
The present paper contains some results about the algebraic setsof planar normal sections associated to the focal manifolds of homogeneous isoparametric hypersurfaces in spheres. With the usual identication of thetangent spaces to the focal manifold with subspaces of the tangent spaces to the isoparametric hypersurface, it is proven that the algebraic set of planarnormal sections of the focal manifold is contained in that of the original hypersurface.